2018
DOI: 10.31234/osf.io/pqg3a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender Bias in Pediatric Pain Assessment

Abstract: Objective: Observer rating of pain is central to diagnosis and treatment in healthcare, especially in pediatrics. However, there are few studies examining potential biases in observer ratings of pediatric pain. Cohen et al. (2014) reported that adult participants rated a video of a child undergoing a needle stick as experiencing more pain when the child was described as a boy as compared to a girl, suggesting a possible gender bias. To confirm, clarify, and extend this finding, we conducted a replication exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…While no study has directly examined how parent ratings of post-concussive symptoms are influenced by children's sex, one study found that adults were more likely to rate boys as experiencing higher levels of pain than girls despite the sexes reporting identical pain ratings (Earp et al 2019). The researchers emphasize that while the adult raters were not parents of the target child and cannot emulate the parent-child relationship, healthcare providers need to be aware of potential gender biases in judgements concerning children's health experiences (Earp et al 2019). Another study found only moderate agreement between child and parent ratings of both somatic and cognitive symptoms (Hajek et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While no study has directly examined how parent ratings of post-concussive symptoms are influenced by children's sex, one study found that adults were more likely to rate boys as experiencing higher levels of pain than girls despite the sexes reporting identical pain ratings (Earp et al 2019). The researchers emphasize that while the adult raters were not parents of the target child and cannot emulate the parent-child relationship, healthcare providers need to be aware of potential gender biases in judgements concerning children's health experiences (Earp et al 2019). Another study found only moderate agreement between child and parent ratings of both somatic and cognitive symptoms (Hajek et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Somatization forms part of the internalizing cluster, alongside depression and anxiety (American Psychiatric Association, ), suggesting that somatic symptoms are psychiatric in nature and can be viewed as the physical expression of psychological distress. Somatic symptoms are nonetheless experienced as physical pain, and gender bias in the assessment of pain begins in early childhood (Earp et al, ). Fundamentally, this suggests that girls are not only more likely to experience frequent somatic symptoms, but are also more likely to have the severity of their symptoms minimized.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, girls perceive the communication of pain as normal when they have pain, while boys perceive that the noncommunication of pain reflects personal strength. This difference between the perceptions of pain communication may also be explained by the fact that boys start to be conscious of the beliefs linked to masculinity, following exposition to explicit sexist stereotypes such as those which state that boys would be more robust and the girls more sensible (Earp et al, 2019). Finally, when these perceptions in line with the pain communication are not taken into account, pain will be ill‐expressed, ill‐interpreted, and thus mismanaged.…”
Section: Discussionmentioning
confidence: 99%